Предмет: Алгебра,
автор: walik4321
Сократите выражение:
a^3-4a^2+5a-20
Ответы
Автор ответа:
0
разложить на множители:
a³-4a²+5a-20=(a³-4a²)+(5a-20)=a²*(a-4)+5*(a-4)=(a-4)*(a²-5)=
=(a-4)*(a²-(√5)²)=(a-4)*(a-√5)*(a+√5)
a³-4a²+5a-20=(a³-4a²)+(5a-20)=a²*(a-4)+5*(a-4)=(a-4)*(a²-5)=
=(a-4)*(a²-(√5)²)=(a-4)*(a-√5)*(a+√5)
Похожие вопросы
Предмет: Литература,
автор: aygulraygul8
Предмет: Математика,
автор: Djevstratova1111
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: 30juiy1975
Предмет: Математика,
автор: Аноним